Fenomena “Financial Influencer” dan Pengaruhnya Terhadap Literasi Keuangan Gen-Z di Kota Padang - Kurnia, Yosi; Octafia, Sri Mona; Hadia, Dina (JOURNAL ECONOMICS AND STRATEGY, 2025)
This study aims to examine the relationship between exposure to financial influencers on social media and financial literacy among Gen Z, considering the role of education as a moderating variable. Financial literacy is analyzed through three main components: financial knowledge, financial attitude, and financial behavior. Using a cross-sectional approach, this study involved 259 respondents aged 15–26 years, with data collected through an online survey. The analysis results indicate that exposure to financial influencers does not significantly affect financial knowledge, regardless of respondents' education levels. Although financial knowledge does not directly influence financial attitudes, both components contribute positively to financial behavior. Additionally, perceived behavioral control has a significant impact on individuals' financial behavior. These findings highlight the need for a more targeted approach to improving financial literacy among young generations, considering factors beyond influencer exposure. Governments, educational institutions, and social media platforms can collaborate to promote more educational financial content. This study contributes to a deeper understanding of the role of financial influencers on social media in shaping Gen Z's financial literacy and expands insights into how various factors, including education, influence individual financial behavior.